Understanding the Transformation of Self-Identity in LPKA Class 1 Tangerang Juvenile Inmates - Achmad Robbi Fathoni (Jurnal Psikologi Teori dan Terapan, 2025)
Background: The process of self-meaning development among juvenile offenders in correctional facilities is crucial to their rehabilitation and reintegration into society. LPKA (Lembaga Pembinaan Khusus Anak) serves as a rehabilitative environment for these individuals, providing educational and psychological programs. Objective: This study aims to explore how juvenile offenders in LPKA Tangerang perceive and interpret their own self-identity after participating in educational programs, and to understand the impacts of these programs on their self-perception. Method: A qualitative phenomenological approach was employed, utilizing in-depth interviews with 5 juvenile offenders who have participated in various educational programs. Data were analyzed using NVivo 12 software to identify key themes regarding self-perception changes, identity formation, and their future outlook. Results: The research found that education in LPKA plays a significant role in altering the self-meaning of juvenile offenders, fostering a more positive self-image and hope for the future. Conclusion: The findings suggest that educational programs in LPKA are effective in reshaping the self-perception of juvenile offenders, contributing to their psychological growth and readiness for reintegration into society. Abstrak Latar Belakang: Pemaknaan diri pada anak binaan di LPKA (Lembaga Pembinaan Khusus Anak) memiliki peranan penting dalam proses rehabilitasi dan reintegrasi sosial mereka. Anak binaan yang mengalami konflik hukum seringkali memiliki pandangan negatif terhadap diri mereka sendiri yang mempengaruhi perilaku mereka. Tujuan: Penelitian ini bertujuan untuk menggali bagaimana anak binaan di LPKA Kelas 1 Tangerang memaknai perubahan diri mereka setelah mengikuti program pendidikan yang ada di sana. Metode: Penelitian ini menggunakan pendekatan kualitatif dengan metode fenomenologi. Data diperoleh melalui wawancara mendalam dengan 5 anak binaan yang telah mengikuti program pendidikan di LPKA. Data dianalisis menggunakan aplikasi NVivo 12 untuk mengidentifikasi tema-tema utama terkait perubahan pemaknaan diri. Hasil: Penelitian ini menemukan bahwa program pendidikan di LPKA berperan signifikan dalam mengubah pemaknaan diri anak binaan, memperbaiki rasa percaya diri, dan membangkitkan harapan untuk masa depan. Simpulan: Temuan ini menunjukkan bahwa pendidikan di LPKA efektif dalam membentuk pandangan positif anak binaan terhadap diri mereka, yang dapat mendukung proses rehabilitasi dan reintegrasi mereka ke masyarakat.